The impact of the PASPOR learning model on pre-service teachers’ mathematical communication skills across initial ability levels - Jufri; Muslim; Pariang Sonang Siregar (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: Therefore, this study aims to examine the effectiveness of the PASPOR learning model in improving students’ mathematical communication skills and to determine whether learning gains differ across initial ability levels. Method: This study employed a quasi-experimental approach using a one-group pretest posttest design. The participants consisted of 62 pre-service elementary teachers enrolled in a mathematics course. Data were collected through a validated mathematical communication test administered before and after the implementation of the PASPOR learning model. The collected data were analyzed using descriptive statistics to describe changes in performance, normalized gain (N-Gain) to measure the magnitude of improvement, and one-way ANOVA to compare learning gains among students categorized into low, medium, and high initial ability groups. Findings: The results indicate a substantial improvement in students’ mathematical communication skills following the implementation of the PASPOR model. The mean score increased from 43.84 in the pretest to 80.65 in the posttest. The average N-Gain of 0.67 indicates a medium-to-high level of improvement. In addition, ANOVA results showed no statistically significant differences in learning gains across initial ability groups (F = 0.536, p = 0.588). Significance: These findings suggest that the PASPOR learning model effectively enhances mathematical communication skills and supports equitable learning improvement among students with diverse initial abilities.